HUBUNGAN PENGETAHUAN KESEHATAN GIGI MULUT DENGAN STATUS KEBERSIHAN RONGGA MULUT PADA LANSIA - Desi Sandra Sari; Yuliana Mahdiyah Daat Arina; Tantin Ermawati (Fakultas Kesehatan Masyarakat, Universitas Jember, 2015)
Oral health among elderly people needs a specially attention because it will affect their general health. A good knowledge of oral hygiene is essential to prevent oral disease. Therefor maintenance of oral hygiene was the best way to maintain the health condition of the elderly people. The purpose of this research was to determine the correlation between oral health knowledge of elderly people with oral health status in the working area ofPuskesmas Kalisat Jember. This study was observasional research on 80 elderly people aged 50-70 years old who came to 12 elderly posyandu of Puskesmas Kalisat Jember. Data were collected by structured questionnaires about oral health knowledge and clinical examination to determine oral hygiene status based on Oral Hygiene Index-simplified (OHIS). Pearson correlation was used for statistical analysis. Most of participant demontratedoral health knowledge score as sufficient category (52,5%) and the oral hygiene status was moderate (57,5%). The correlation between the level of oral health knowledge with OHI-S index was significant (p< 0,05). Among elderly people, the knowledge of oral health correlated with the oral hygiene.Keywords: elderly, dental health, Index OHI-S, Puskesmas Kalisat Jember